Influence of growth conditions on structural parameters of scheelite PbTO4 (T = Mo, W) crystals. (5th May 2016) - Kaurova, I.A.; Kuz'micheva, G.M.; Brykovskiy, A.A.; Rybakov, V.B.; Gorobets, Yu.N.; Shekhovtsov, A.N.; Cousson, A.
Abstract: Lead molybdates and tungstates with general chemical formula PbTO4 (PTO), where T is Mo (PMO) or W (PWO), were grown by the Czochralski method in an oxygen (PTO-A) or inert (PTO-N2 ) atmosphere from a stoichiometric mixture of corresponding oxides or mixture containing an excess of PbO (PMO-N2 (Pb)). The crystals were investigated by X-ray and neutron single crystal and X-ray powder (Rietveld method) diffraction methods. For PWO-A and PWO-N2 crystals, the presence of additional reflections (50%) was revealed, indicating the symmetry reduction from space group I 41 / a to I 4 _ caused by kinetic (growth) order–disorder phase transition associated with an ordering/disordering of oxygen vacancies. In the structures of PMO samples, the vacancies are absent in the Mo and O sites (PMO-A and PMO-N2 ) and they are present in the Pb sites (except for PMO-N2 (Pb)); the defect content being higher in the PMO-N2 crystal grown in an inert atmosphere. It is shown that the light yellow color of PTO crystals is due to the O and Pb vacancies, that may be accompanied by the transition Pb 2 + → Pb 3 +, and the gray-purple color of PMO-N2 (Pb) is due to the transition Mo 6 + → Mo 5 + . Graphical abstract: Highlights: PbTO4 (T = Mo, W) crystal structures were refined by neutron and X-ray diffraction. Symmetry reduction from space group I 41 / a to I 4 _ was first found for PbWO4 crystals. The type and concentration of point defects were determined. Coloration is caused by the Pb and O vacancy formation and Mo 6 + → Mo 5 + transition.